2019
DOI: 10.3389/fonc.2019.00309
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and Clinical Value of CD44 in Colorectal Cancer: A Meta-Analysis

Abstract: Background: CD44 is widely used as a putative cancer stem cells (CSCs) marker for colorectal cancer (CRC). However, the prognostic role of CD44 in CRC remains controversial. Methods: We performed a systematic review and meta-analysis to evaluate the association of various CD44 isoforms and overall survival (OS) and clinicopathological features of CRC patients. Results: A total of 48 studies were included in the meta-analysis. Total CD44 isoforms overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 91 publications
2
84
0
1
Order By: Relevance
“…CD44 is a transmembrane glycoprotein that has been recognized as a CSC marker in a variety of cancers [44]. In CRC, CD44 overexpression is related to poor differentiation, lymph node metastasis and distant metastasis [45]. CD133, also known as prominin-1, is negatively correlated with OS in CRC patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 is a transmembrane glycoprotein that has been recognized as a CSC marker in a variety of cancers [44]. In CRC, CD44 overexpression is related to poor differentiation, lymph node metastasis and distant metastasis [45]. CD133, also known as prominin-1, is negatively correlated with OS in CRC patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…58 In contrast, the authors of a recent meta-analysis concluded that CD44 overexpression in colorectal carcinoma is an unfavorable prognostic factor that predicts a high grade and metastases in lymph nodes and distant sites. 59 Hong et al reported on 162 immunohistochemically investigated colorectal cancer cases. This team did not find statistically significant associations between pT (p = 0.578), pTNM stage (p = 0.711), G (p = 0.144) or age (p = 0.690).…”
Section: Discussionmentioning
confidence: 99%
“…CSCs display elevated ability to cope with cellular stresses including resistance to chemotherapeutic agents and highly activated DNA damage response (DDR) [7] . CD44, CD133, EpCAM, or ALDH are established as CSC markers for various cancers [8] , [9] , [10] , [11] . Expression of these markers is associated with recurrence and death.…”
Section: Introductionmentioning
confidence: 99%